Overview of diffusion boriding problems in industrial applications - Željko Stojanović; Sanja Stanisavljev (Zaštita Materijala)
In this paper is systematized a review of the problem which occur during the execution of the boriding process, and which by its occurrence limit its wider and versatile industrial application. The paper focuses on all defects that undermine the integrity of the boride layer and which affect on the reduction of its safety in severe exploitation conditions. The research was directed towards the display of limitations and inadequacy of boriding procedures in a solid, liquid and gaseous medium in terms of their contribution to low production efficiency and unjustifiably high production costs. The adverse effects of brittleness and formation of cracks that lead to fracture and peeling of the boric layer were considered, the problems of choosing high process temperatures which can be harmful for the base material, but also other errors which to be avoided in order to achieve the optimum characteristics of the boride layers. Remaining in this context, special attention was paid to the frequent factors that have the greatest impact on the deterioration of the mechanical properties of boride layers, especially dynamic strength and toughness.